Aplikasi Termokopel untuk Pengukuran Suhu Autoklaf - Agatha Mahardika Anugrayuning Jiwatami (Universitas PGRI Semarang, 2022)
Autoclave is a tool used to sterilize medical instruments such as surgical knives and scissors. The process of autoclave sterilization is to provide heat energy to the autoclave. Hot steam will rise into the closed chamber. The control system will monitor the temperature until the required temperature is reached (121-124 °C). Temperature measurement in the autoclave is done using a thermocouple sensor. Temperature testing is done by comparing temperature measurements using a thermocouple and a mercury thermometer. Testing with a thermocouple produces output that is linear and comparable to measurements using a mercury thermometer. The correlation coefficient value of the measurement results using a mercury thermometer is 0.99982 and a thermocouple is 0.99894. Furthermore, the test is carried out by looking at the change in the line on the indicator tape to the length of time for sterilization in the autoclave chamber. As a result, the longer the sterilization time, the change in the line on the indicator tape will look darker, which indicates the sterilization process is going well.Keywords: temperature measurement, autoclave, type K thermocouple, indicator tape